HUMANITARIAN CRISIS IN YEMEN: STUDY OF A SOCIAL SEMIOTIC M.A.K HALLIDAY ON ALJAZEERA.NET NEWS - Luthfiyyah, Nurul; Muassomah, Muassomah (Jurnal Riset Mahasiswa Dakwah dan Komunikasi, 2025)
The food and humanitarian crisis in Yemen, caused by prolonged war, has left millions suffering from hunger, disease, and dependence on international aid. Children and women are the most vulnerable groups. This situation is worsened by funding shortages for humanitarian organizations and the impacts of climate change. The research employs a qualitative descriptive method to identify linguistic phenomena within the text by collecting data from books, journals, the internet, and other written literature. The findings, based on M.A.K. Halliday's semiotic theory, reveal that the Al Jazeera news article titled "Qissatun Yamaniyyin ma'a an-nuzūḥ wa al-jū'... intizhārun mu'limun limusā'adātin ghābat 'āmayn" highlights three main focuses (field of discourse): the decline in UN aid, the displacement story of Youssef Mohammed, and the suffering of citizens. The tenor of discourse by Youssef Mohammed, Julien Harneis, and Fatik al-Radini represents international institutions, supported by four modes of discourse that visually reinforce the news content.